Husband Support on Pregnant Mother's Anxiety in Facing Labor During the Covid-19 Pandemic in Tamanan Kediri 2022 - Meirna Eka Fitriasnani; Rahma Kusuma Dewi; Siti Aminah; Tira Gustiara Dewi; Dwi Ayu Lestari (Journal of Global Research in Public Health, 2022)
Husband's support is a very important factor in the delivery process, because the husband can foster feelings of confidence and form a strong mentality towards his wife so that anxiety and fear disappear. In addition, cooperation between family and husband in providing good support for pregnant women can also eliminate the worry of pregnant women about the delivery process that will be carried out by pregnant women. The design of this research is correlational analytic. The population in this study were pregnant women in Tamanan Village, Kediri City in May 2022.  In this study, the sampling technique used simple random sampling The research instrument is a questionnaire sheet.The results showed that half (50%) of the respondents who received good husband support experienced mild anxiety, namely as many as 6 respondents, almost all (76.92%) who received sufficient husband support experienced moderate anxiety, namely as many as 20 respondents. Based on the results of statistical tests using the Spearman Rank correlation test (Rho) on the husband's support variable (X) and anxiety level (Y) obtained ρ value = 0.002 with a confidence level of α = 0.05, it can be concluded that ρ < α then H0 is rejected and H1 is accepted, meaning that there is a relationship between husband's support and anxiety levels in third trimester pregnant women. Based on the results of the study, there was an effect of husband's support on the anxiety of pregnant women in the third trimester in facing childbirth during the covid 19 pandemic in Tamanan Village, Kediri City in 2022. Suggestions for research sites to motivate husbands to increase their role psychologically throughout the process experienced by their wives includes pregnancy, childbirth, postpartum to the decision-making process in family planning.